ANALISIS YURIDIS PERTIMBANGAN HAKIM DALAM MEMBERIKAN IZIN HAK ASUH ANAK KEPADA ORANG TUA ASUH (STUDI PUTUSAN PENGADILAN AGAMA LUBUK PAKAM NOMOR 706/PDT.G/2018/ PA.LPK DAN PUTUSAN NOMOR 943/PDT.G/2014/PA.LPK) - NURUL TAJAWALIYAH (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Dr. Utary Maharani Barus, SH, MHum2. Dr. Yefrizawaty, SH, MHum3. Dr. Idha Aprilyana, SH, MHum Child care is the fulfillment of various aspects of a child's primary and secondary needs. Child care covers various aspects, namely education, living costs for health, peace and all aspects related to their needs. Today child custody is often a problem before or after a husband and wife conflict, even if it is not uncommon for ex-husbands and ex-wives to fight for their children's custody, because children are the hopes of parents who are difficult to separate. The problem raised in this study, namely how the legal arrangements for child custody in the event of a divorce between husband and wife according to the Compilation of Islamic Law, how the judge's legal considerations in granting child custody permission in the Lubuk Pakam Religious Court Decision Number 706/Pdt.G/2018/PA. Lpk, and the Decision of the Lubuk Pakam Religious Court Number 943/Pdt.G/2014/PA. Lpk, and how the legal consequences arise from granting child custody permits by judges to applicants for child custody.Keywords: Licensing, Fostering Rights, Children, Divorce, Religious Courts.